Commonly Used Assessment Method To Evaluate Mental Workload For Multiple Driving Distractions: A Systematic Review - Nurainaa Kabilmiharbi; Nor Kamaliana Khamis; Nor Azila Noh (Tehran University of Medical Sciences, 2024)
Indexed by WOS/ERA